Unravelling secularization: an international study - Pablo Bra\~nas-Garza; Teresa García-Mu\~noz; Shoshana Neuman (Institute for the Study of Labor (IZA), 2007)
The current study examines individuals who were raised in a certain religion and at some stage of their life left it. Currently, they define their religious affiliation as 'no religion'. A battery of explanatory variables (country-specific ones, personal attributes and marriage variables) was employed to test for the determinants of this decision. It was found that the tendency of individuals to leave their religion is strongly correlated with the degree of strictness of their country and with their spouse's religious characteristics. Moreover, personal socio-demographic features seem to be less relevant.
Keywords: Z12; 300; Religion; convert-out; church attendance; prayer; parental religiosity; Europe; Weltanschauung; Religionsgemeinschaft; Mitgliedschaft; Persönlichkeitspsychologie; Politisches System; Lebensgemeinschaft; Welt